Online Prostitution in Banten: Critical Studies on Criminology and Criminal Law: Prostitusi Online di Banten: Kajian Kritis Kriminologi dan Hukum Pidana - Fathurokhman, Ferry; Fauzi, Ahmad (LITIGASI, 2025)
This research is based on the hypothesis that online prostitution exists and is easily found in the Banten region. Two main issues are discussed in this study: first, what factors lead someone to become an online commercial sex worker in Banten? Second, how can criminal law address online commercial sex workers? This study combines empirical and normative research. Primary data collection was conducted through various dating applications. Primary data was obtained directly from online commercial sex workers spread across Banten through interviews conducted at restaurants, cafes, rented houses, and hotel lobbies. The research findings reveal that economic factors, divorce, religious understanding, and weak law enforcement contribute to the widespread occurrence of online sex worker transactions in Banten. Criminal law does not classify sex workers as offenders due to the role bias between perpetrator and victim. However, under Law Number 1 of 2023 concerning the Criminal Code and several other laws, sex workers can be subject to criminal legal norms, although some of these cases fall under the category of complaint-based offenses. The research concludes that online sex workers in Banten are very easy to find. The government has a role and responsibility in addressing the rise of online prostitution in Banten. All respondents who chose the path of online prostitution through dating applications are individuals who adapt through innovation—desiring success, money, and other benefits but using unlawful means. A specific legal norm is needed to regulate online sex workers without requiring interpretation.